Drug Therapy Problem Severity Following Hospitalization and Association With 30-Day Clinical Outcomes. Issue 12 (December 2018) - Westberg, Sarah M.; Yarbrough, Angela; Weinhandl, Eric D.; Adam, Terrence J.; Brummel, Amanda R.; Reidt, Shannon L.; Sick, Brian T.; St. Peter, Wendy L.
Background: Improved understanding of how drug therapy problems (DTPs) contribute to rehospitalization is needed.Objective: The primary objectives were to assess the association of DTP likelihood of harm (LoH) severity score, as measured by comprehensive medication management (CMM) pharmacist after hospital discharge, with 30-day risk of hospital readmission, observation visit, or emergency department visit, and to determine whether resolution of DTPs reduces 30-day risk. Secondary objectives were to determine if any eventswere associated with DTPs and preventability of events.Methods: Data were collected for 365 patients who received CMM following hospitalization and had at least 1 DTP identified. Retrospective chart reviews were completed for 80 patients with subsequent events to assess associationg with a DTP and its preventability.Results: For each 1-point increment in maximum LoH score, there was 10% higher risk of the composite end point (hazard ratio [HR]=1.10; 95% CI:0.97-1.26; P =0.13). When DTPs were resolved by the CMM pharmacist, the association was attenuated, with a HR of 1.15 (95% CI:0.96-1.38; P =0.12) when the DTP was unresolved and HR of 1.09 (95% CI:0.96-1.25; P =0.52) when resolved; for hospital readmission alone, the corresponding HRs were 1.23 (95% CI:1.00-1.53; P =0.05) and 1.05 (95% CI:0.87-1.27; P =0.60). Of 80 subsequent events, 44 were associated with a medication; 22 were considered preventable.Conclusion and Relevance: The LoH severity score was associated with risk of 30-day events. The strength of association was attenuated when DTPs were resolved by the CMM pharmacist. However, because of statistical uncertainty, larger studies are needed to confirm these patterns.